Analisis media pembelajaran digital pada mata pelajaran IPAS dalam implementasi kurikulum merdeka di sekolah dasar - Haniifah Alyaa Azmiira Rosyid; Sri Marmoah; Fadhil Purnama Adi (Universitas Sebelas Maret, 2025)
The purpose of this study was to describe of digital learning media to IPAS subjects in implementation of merdeka belajar curriculum at Elementary Schools. This is qualitative descriptive research using a case study approach. The results of this study show that in the application of digital learning media, teacher have met the criteria for the selection of learning media that are dictated by the term ACTION (Access, Cost, Technology, Interactivity, Organization, Novelty) well, although in the use of the machine there are some less optimum aspects, i.e. on the access and technology aspects. In the access aspect, teachers can use digital learning medium well, while for the students there is still difficulty in accessing the digital Learning media caused by several factors among them: not getting the opportunity to access the learning media when learning in school, not getting used to digital technology, lack of technology support facilities at home. Then in the technology aspect, schools have provided sufficiently complete technology facilities but with an unoptimal number, only available 4 laptops, 2 LCD Projectors and 1 sound used alternately between classes.